ICT Thematic Science Teaching Material with 5E Learning Cycle Model to Develop Students' 21st-Century Skills - Asrizal, A.; Yurnetti, Y.; Usman, E. A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Twenty-first-century learning should develop students’ 21st-century skills, including aspects of knowledge, attitudes, character, and 4C skills. These students’ skills need to be widely developed in science learning to handle the challenges of this century. The preliminary study results indicate that integrating learning materials in science learning and students’ 4C skills were low. Thematic science teaching materials integrated the 5E learning cycle model can solve the problem. The study aims to investigate the effect of thematic science teaching material integrated with the 5E on various aspects of students’ 21st-century skills, including knowledge, attitudes, and 4C skills. The research method is quasi-experimental, and the design is a randomized control group posttest-only, which is suitable for determining the effect of a treatment on a dependent variable. The knowledge aspect is measured using a written test sheet in multiple-choice, the attitude aspect using an observation sheet, and the 4C skills aspect using a performance assessment sheet. Data were analyzed using a comparison test for the two sample groups and the Mann-Whitney U test. The data analysis state that the application of thematic science learning material integrated with the 5E has a positive effect on students’ 21st-century skills, including aspects of knowledge, attitudes, and 4C skills: critical thinking skills, creative thinking skills, and communication skills. The study concludes that applying thematic science learning material integrated with the 5E learning cycle model effectively develops the three aspects of students’ 21st-century skills.